(untitled) (Conference on English Language Teaching, 2023)
ChatGPT is frequently prescribed as a valuable tool for language teaching with its ability to generate human-like responses and engage in interactive conversations. This research study explores language teachers’ perspectives on ChatGPT as a resource for language teaching. The study investigates the perceived benefits, challenges, pedagogical considerations, and specific ways language teachers utilize ChatGPT in their instructional practices. To address these questions, a mixed-methods research design was employed. Language teachers from diverse educational settings participated in a survey. Thematic analysis was used to analyze the qualitative data, while descriptive statistics were applied to analyze the quantitative data. The findings of this study shed light on the perceived benefits of ChatGPT, such as increased efficiency in lesson planning and additional language input for learners. On the other hand, teachers faced concerns about accuracy, reliability, and potential overreliance on technology. Moreover, the study explores how language teachers evaluate the pedagogical effectiveness of ChatGPT, considering factors such as learner engagement, language proficiency, and the alignment of ChatGPT-generated content with learning objectives. Overall, this study’s results enhance understanding of the language teachers’ perspectives regarding ChatGPT, facilitating informed discussions and further exploring its potential role and impact in language teaching contexts.